New 24 polymorphic DNA microsatellite loci for the major malaria vector Anopheles darlingi and transpecies amplification with another anophelines - Lima, G. N.; Batista, Jacqueline da Silva; Formiga, Kyara M.; Cidade, Fernanda Witt; Rafael, Míriam Silva; Tadei, Wanderli Pedro; Santos, Joselita Maria M. (Conservation Genetics Resources, 2010)
Anopheles darlingi is a major human malaria vector in the Neotropics. Twenty-four polymorphic microsatellite loci were isolated and characterized in 21-32 individuals collected in Coari (Amazonas, Brazil). The number of alleles per locus ranged from 4 to 11 (average of 7.667). The observed heterozygosity (H O) varied between 0.037 and 0.833 (average of 0.500), while the expected heterozygosity (H E) ranged from 0.177 to 0.871 (average of 0.723). Thirteen loci showed a significant deviation from HWE. No linkage disequilibrium was found between the loci. © Springer Science+Business Media B.V. 2010.
Keywords: Anopheles Darlingi